EVALUASI PROGRAM KELOMPOK KERJA GURU GUGUS MAWAR KECAMATAN BELITANG III KABUPATEN OGAN KOMERING ULU TIMUR - B A - INDRIASARI (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2018)
This reseaCrh was done to get information about effectiveness of KKG Gugus Mawar Programs using CIPP evaluation model. Data technique analysed used descriptive qualitative analysed. The result of this research show that (1) context component include of very good categories and recommended to keep the qualityof implementations; (2) input component include of very good categories and recommended to keep the quality of implementations; (3) process component include of very good categories and recommended to keep the quality of implementations; and (4) product component include of very good categories and recommended to keep the quality of implementations. According to the result of research, KKG Gugus Mawar program include of very good categories and recommended to keep the quality of implementation.